2018
DOI: 10.1177/1747021817737520
|View full text |Cite
|
Sign up to set email alerts
|

The influence of short-term language-switching training on the plasticity of the cognitive control mechanism in bilingual word production

Abstract: This study examined the effect of short-term language-switching training on the cognitive control mechanism in bilingual word production. In two experiments, two groups of relatively proficient but unbalanced Chinese-English bilinguals performed a cued picture-naming task, in which they switched between their two languages. On two consecutive days, the participants took part in four sessions. The same procedure was employed on 2 days in Experiment 1, whereas the cue-language mapping was reversed on Day 2 in Ex… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

5
31
1

Year Published

2019
2019
2022
2022

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 19 publications
(37 citation statements)
references
References 48 publications
5
31
1
Order By: Relevance
“…The present results also showed reversed language dominance: faster responses when naming in L2 than in L1 in mixedlanguage blocks. The reversed language dominance has been reported in studies examining unbalanced bilinguals (e.g., Costa and Santesteban, 2004;Christoffels et al, 2007;Gollan and Ferreira, 2009;Verhoef et al, 2009;Peeters et al, 2014;Kleinman and Gollan, 2016;Peeters and Dijkstra, 2018;Wu et al, 2018;Liu et al, 2019;Peeters, 2020). The present study showed a global slowdown of the L1 across semantic conditions in switch trials.…”
Section: Language Switching: Mixing Costs Reversed Language Dominancsupporting
confidence: 81%
“…The present results also showed reversed language dominance: faster responses when naming in L2 than in L1 in mixedlanguage blocks. The reversed language dominance has been reported in studies examining unbalanced bilinguals (e.g., Costa and Santesteban, 2004;Christoffels et al, 2007;Gollan and Ferreira, 2009;Verhoef et al, 2009;Peeters et al, 2014;Kleinman and Gollan, 2016;Peeters and Dijkstra, 2018;Wu et al, 2018;Liu et al, 2019;Peeters, 2020). The present study showed a global slowdown of the L1 across semantic conditions in switch trials.…”
Section: Language Switching: Mixing Costs Reversed Language Dominancsupporting
confidence: 81%
“…As previously noted, however, this previous research examined language switching practice involving cued picture naming only with either balanced bilinguals (Catalan-Spanish, Timmer et al, 2019) or L2 learners (Chinese-English, Spanish-English, Kang et al, 2018;Prior & Gollan, 2011;Wu et al, 2018). Furthermore, the effectiveness of the practice in reducing switch costs was measured using averaged switch costs per session only, without examining learners' item-by-item performance over the course of each practice session.…”
Section: Training Language Selection Mechanismsmentioning
confidence: 99%
“…First, language-switching practice improved performance on post-practice, non-linguistic inhibitory control tasks (e.g., colour-shape decision task in Timmer et al, 2019; AX-CPT in Zhang et al, 2015). Second, some evidence indicates that switch costs reduced during the practice (Timmer et al, 2019; Wu et al, 2018; Zhang et al, 2015). Taken together, these results indicate that short-term practice that required learners to regularly switch between L1 and L2 improved inhibitory control mechanisms, which, furthermore, appeared to translate into improved language selection abilities, as evidenced by reduced switch costs.…”
Section: Training Language Selection Mechanismsmentioning
confidence: 99%
See 2 more Smart Citations